2019
DOI: 10.21273/hortsci13293-18
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Association of Multi-scale Architectural Traits with Canopy Volume and Yield: Moving Toward High-density Systems for Macadamia

Abstract: Additional index words. path analysis, plant architecture, planting density, intensification, vigor, productivity Abstract. The vigorous growth and large canopy size of commercial macadamia (Macadamia integrifolia, M. tetraphylla, and hybrids) cultivars generally restricts macadamia orchards to low-density planting. Little is known of the detailed interactions between plant architecture and yield components specific to macadamia. This chapter examines how dependent traits such as canopy size and yield might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Areas of research included propagation, tree physiology, soils and nutrition, pollination biology, pest and disease biology, orchard management, genetics and breeding, developing production areas, and product development. Seven of the presentations are published in this special section Hardner et al, 2019;Howlett et al, 2019;O'Connor et al, 2019;O'Hare et al, 2019;Toft et al, 2019;Zhao et al, 2019).…”
Section: Summary Of Presentationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Areas of research included propagation, tree physiology, soils and nutrition, pollination biology, pest and disease biology, orchard management, genetics and breeding, developing production areas, and product development. Seven of the presentations are published in this special section Hardner et al, 2019;Howlett et al, 2019;O'Connor et al, 2019;O'Hare et al, 2019;Toft et al, 2019;Zhao et al, 2019).…”
Section: Summary Of Presentationsmentioning
confidence: 99%
“…Several presentations (J. Wilkie et al, personal communication; T.G. Thorp and A. Smith, personal communication; B. Toft et al, personal communication) (Toft et al, 2019) discussed the physiology of young (<4 years of age) trees to support development of a new high-density intensive production system and underpin greater productivity. Early yield per tree (and per hectare) was 50 times greater for the cultivar A203 than HAES 741 at age 4, primarily due to early flowering (J. Wilkie et al, personal communication) (Fig.…”
Section: Summary Of Presentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few other studies have measured these component traits on a diverse collection of germplasm. In their study of 15 varieties and selections at 4-5 years since planting, Toft et al (2019) found that phenotypes for RL ranged from 2-46 cm, with an average of 16 cm, whilst NPR varied from 0.2-2.6. These findings do not reflect the phenotypic ranges observed in the current study (RL 3.6-32.3 cm, NPR 1-10.4), which may be explained by different germplasm, environments and slightly different measuring techniques.…”
Section: Variability and Heritability Of Yield And Yield Component Trmentioning
confidence: 99%
“…However, cultivars with thin shells may have lower kernel quality due to defects caused by damaging pests and diseases (Hardner et al 2009). With the focus turning towards smaller trees with high yields, planting densities, and, consequently, yield per hectare, are likely to increase (Toft et al 2019). Trunk circumference (stem girth) or trunk cross-sectional area, are easily-measured traits commonly used as an estimate of tree size (Hardner et al 2002;Toft et al 2018); trunk size may affect nut yield due to uptake of resources available for growth and fruit production.…”
Section: Introductionmentioning
confidence: 99%